Heliostat aiming point optimization for external tower receiver. (15th November 2017) - Astolfi, Marco; Binotti, Marco; Mazzola, Simone; Zanellato, Luca; Manzolini, Giampaolo
Highlights: We focus on the heat flux profile optimization for solar tower central receiver. We propose a number of novel aiming strategies for heliostat pointing. Heat flux peak is strongly reduced compared to other strategy in literature. We extend the validity of our approach with sensitivity analyses. Abstract: Reduction of peak fluxes on solar receiver is an important research topic because peak minimization can lead to lower receiver temperatures with advantages in terms of thermal efficiency and mechanical stresses. This work proposes different approaches for the minimization of the heat flux on external tower receiver with surround field. The mathematical formulation is implemented in Matlab, while Delsol is used for the heliostat field modeling. Since the number of variables is very high, branching the original optimization problem in a set of sub-problems is a beneficial technique. Four approaches, based on this concept, are here proposed: they differ for the number of field sectors considered in the optimization process and on the heliostat projection modeling. The best approach, which considers the overlapping effect between adjacent sectors, can reduce the peak flux down to 770 kW/m 2 in 120 s of computational time. This value is about 15% lower than reference aiming strategies available in literature. The optimized flux is almost flat in the central part of the receiver while it has significant gradient at the lower and upper border. Finally, a sensitivity analysis shows that the proposed approaches work well at any given solar position and with different heliostat assumptions (i.e. curvature and errors).